2010
DOI: 10.1007/s11258-010-9784-z
|View full text |Cite
|
Sign up to set email alerts
|

Phenology of Pilosocereus leucocephalus (Cactaceae, tribe Cereeae): a columnar cactus with asynchronous pulsed flowering

Abstract: Pilosocereus leucocephalus produces flowers in discrete pulses, suggesting this cactus might exhibit pulsed flowering-a rare flowering pattern among angiosperms. In this study, we (1) describe the phenology of P. leucocephalus, (2) explore the influence of temperature, rainfall, and plant size on the flowering pattern, and (3) assess the effect of flowering phenology on the reproductive success of this cactus. Flowering phenology was characterized using the coefficient of variation in addition to traditional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
10

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 30 publications
0
13
0
10
Order By: Relevance
“…The results of previous studies in columnar cacti have suggested that reproductive activity is mainly controlled by variations in one primary factor, either temperature or rainfall (Bowers 1996;Ruíz et al 2000;Petit 2001;Bustamante and Búrquez 2008;Munguías-Rosas and Sosa 2010). That was not the case for H. portoricensis, which exhibited very shortterm increments in bud production in response to proportional increments in mean and minimum temperatures and where subsequent rainfall events appear to be an environmental cue necessary to break the dormancy of buds and induce flowering.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results of previous studies in columnar cacti have suggested that reproductive activity is mainly controlled by variations in one primary factor, either temperature or rainfall (Bowers 1996;Ruíz et al 2000;Petit 2001;Bustamante and Búrquez 2008;Munguías-Rosas and Sosa 2010). That was not the case for H. portoricensis, which exhibited very shortterm increments in bud production in response to proportional increments in mean and minimum temperatures and where subsequent rainfall events appear to be an environmental cue necessary to break the dormancy of buds and induce flowering.…”
Section: Discussionmentioning
confidence: 98%
“…Studies performed with different cactus species have demonstrated that the timing and intensity of the reproductive phenological patterns are principally affected not only by variation in rainfall (i.e., the start of the rainy season and total annual precipitation) but also by temperature variation (i.e., annual mean minimum and spring mean maximum temperatures) (Bowers 1996;Pavón and Briones 2001;Petit 2001;Bustamante and Búrquez 2008). In the case of columnar cacti, the relative influence of rainfall and temperature on phenology is not uniform across the species that have been studied, and their effects on reproductive timing can be positive, negative, or even nil (Bowers 1996;Ruíz et al 2000;Petit 2001;Bustamante and Búrquez 2008;Munguías-Rosas and Sosa 2010). For example, reproductive onset (triggering budding and flowering phenologies) and reproductive output of Cargenia gigantea in the northern Sonoran Desert (Arizona, USA) show a positive association with winter rainfall intensity (Bowers 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Some basics of the role of animals in its frugivory networks are unknown (Munguía-Rosas & Sosa, 2010), and the first few questions of importance in understanding these relationships include: Which species of animals are frugivores of P. leucocephalus? What is the relative importance of each guild/species in removing its fruit pulp?…”
Section: Frugivory Is a Complex Ecological Process Influenced By Mumentioning
confidence: 99%
“…This Mesoamerican species, as well as many others in all four clades of columnar cacti, has received little attention from researchers in spite of its keystone position in tropical dry ecosystems. Some basics of the role of animals in its frugivory networks are unknown (Munguía‐Rosas & Sosa, ), and the first few questions of importance in understanding these relationships include: Which species of animals are frugivores of P. leucocephalus ? What is the relative importance of each guild/species in removing its fruit pulp?…”
Section: Introductionmentioning
confidence: 99%
“…En algunos bosques tropicales caducifolios y trópicos secos los cactus columnares son especies muy conspicuas, aunque han sido poco estudiadas (Bullock 2000, Delgado-Fernández et al 2017, Munguía-Rosas & Sosa 2010, Vázquez-Castillo et al 2019, y aún se desconoce sobre su dinámica poblacional y el tipo de reclutamiento en ambientes más húmedos que se caracterizan por tener temporada de lluvia totalmente predecible. Por ejemplo, en la estación biológica de Chamela la precipitación promedio anual es de 731 mm (Ayala 2016) y en la selva baja caducifolia del centro del estado de Veracruz hay registros de 750 mm promedio anual (Trejo-Vázquez 1999).…”
unclassified